ACOUSTIC EMISSION SENSORS, INTENDED FOR RESEARCH OF CUTTING - Девін, Л. М.; Стахнів, М. Е.; Бачкало, О. І. (Science-based technologies, 2009)
The method of calibrating of acoustic emission sensors, intended for research of cutting, is considered, utilizing of high-frequency spectrum analyzer.